Sharia Compliance Versus Consumer Protection: Legal Ambiguities of Fintech Paylater in Muslim Societies - Halili; Zulfahmi; Rudiadi; Wildan Miftahussurur (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
The rapid expansion of financial technology has transformed consumer credit markets in Muslim societies, particularly through the proliferation of Buy Now Pay Later (paylater) services. While these digital deferred payment schemes are often promoted as flexible and Sharia-compliant alternatives to conventional credit, their legal positioning remains deeply contested. This article examines the legal ambiguities surrounding fintech paylater by analysing the tension between Sharia compliance and consumer protection within contemporary regulatory frameworks. Drawing on qualitative doctrinal and regulatory analysis, the study engages with Islamic legal discourse, consumer protection law, and fintech governance literature to explore how legal legitimacy is constructed and contested in digital financial markets. The findings demonstrate that Sharia compliance in fintech paylater is predominantly established through contractual formalism, focusing on permissible legal forms rather than substantive economic and behavioural outcomes. This approach, while facilitating regulatory acceptance, often fails to address consumer vulnerabilities arising from information asymmetry, over-indebtedness, and penalty-based revenue structures. Moreover, the study reveals that fragmented governance characterised by the institutional separation of financial regulators, consumer protection authorities, and Sharia governance bodies plays a central role in sustaining legal ambiguity. Compliance with religious norms does not necessarily translate into effective consumer protection, allowing fintech providers to navigate regulatory boundaries selectively. By foregrounding legal ambiguity and governance fragmentation, this article contributes to scholarly debates on Islamic fintech regulation and consumer law. It challenges the assumption that formal Sharia compliance inherently ensures ethical financial practices and argues for integrated regulatory approaches that reconcile religious legitimacy with substantive consumer protection. The study offers conceptual insights relevant to legal scholars, policymakers, and regulators grappling with the complexities of digital deferred payment systems in Muslim societies.